Customer Satisfaction in Indonesia's Retail Industry: Economic Antecedents and Business Consequences - Dewi, Sandra; Berlianto, Margaretha Pink (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study wants to find out how things like product variety, perceived price, store design, store atmosphere, customer service, and convenience affect how satisfied customers are. It also looks at how customer satisfaction affects whether they will buy from the store again. This study uses numbers and statistics to do this. The study collected information from 232 people using a questionnaire on Google Forms. These people were customers of Flying Tiger Copenhagen in Indonesia. The study used a method called SEM PLS to analyze the data. This included testing how well the data was measured, the relationships between different factors, and the study's main ideas. The results showed that product variety, perceived price, store atmosphere, customer service, and convenience all make customers satisfied. But store design actually made customers less satisfied. Also, satisfied customers were more likely to buy from the store again.